The native point defects in C14 Mg2Ca Laves phase: A first-principles study. (October 2015) - Shao, Lin; Shi, Tao-Tao; Zheng, Jie; Pan, Xiong-Ze; Tang, Bi-Yu
Abstract: The native point defects in C14 Mg2 Ca Laves phase are studied from the first-principles density functional theory calculations within GGA approximation. The defect formation energies indicate that anti-site defects are energetically favored over vacancies. Under Mg-rich and even general Ca-rich condition, defect MgCa of Mg anti-site on Ca sublattice is favorable owing to the lowest formation energy. The CaMg2 defect of Ca anti-site on Mg2 sublattice is also likely dominant only under extreme Ca-rich environment. The present results could explain reasonably the asymmetric off-stoichiometry of Mg2 Ca. The effective point defect concentrations of Mg2 Ca as a function of composition and temperature at experimental range are also calculated from a canonical statistical model, and the derived results show a linear relationship between the logarithm of defect concentration and T −1 . Geometrical factor is further studied, and it is found that atomic size possesses an obvious influence on the structure of point defect in Mg2 Ca. The electronic feature is further studied to reveal underlying mechanism for formation of point defects. Highlights: Defect formation energy indicates that the anti-site defect MgCa is most favorable. The anti-site defects are energetically favored over vacancies. The present study explains experimentally observed off-stoichiometry in Mg2 Ca. The atomic size obviously affects the point defect structures in Mg2 Ca. The electronic structure reveals the underlying mechanism of defect structure.